2009
DOI: 10.6090/jarq.43.137
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the 1998 Forest Fire on Ectomycorrhizae of Dipterocarp Trees and their Recovery in Tropical Rain Forests of East Kalimantan, Indonesia

Abstract: The impact of forest fire in 1997 and 1998 on the mycorrhzae was studied at the dipterocarp forest in East Kalimantan, Indonesia. In unaffected forest more than half of total ectomycorrhizae distributed in the organic layer but in the fire-affected forest one and a half years after the fire, total amount of mycorrhizae was smaller and they were found in deeper soil. The number of morphotypes of mycorrhizae was also smaller in fire-affected forest. An artificial plantation established after clear cut and prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…RESPONSES TO BURNING.-Tata et al (2003) did not find any EcM fruit bodies in forests burnt in 1998 in East Kalimantan (examined in 2000) and, using two dipterocarp seedling species as bait plants, she found that there was no difference in the proportion of seedlings with EcM (although values for both species were low at around 5%) among seedlings grown in the burnt and unburnt forest soils. In contrast, Akema et al (2009) found that in a severely burnt site (examined in 2002) there were no EcM root tips in the soil, although there were some fruiting bodies of typically early stage fungi (Laccaria vinaceoavellana). In the moderately burnt site, four EcM morphotypes were found, with dominance by one species, compared to a much more even EcM community in undisturbed forest where eight morphotypes were found.…”
Section: Commmentioning
confidence: 89%
See 2 more Smart Citations
“…RESPONSES TO BURNING.-Tata et al (2003) did not find any EcM fruit bodies in forests burnt in 1998 in East Kalimantan (examined in 2000) and, using two dipterocarp seedling species as bait plants, she found that there was no difference in the proportion of seedlings with EcM (although values for both species were low at around 5%) among seedlings grown in the burnt and unburnt forest soils. In contrast, Akema et al (2009) found that in a severely burnt site (examined in 2002) there were no EcM root tips in the soil, although there were some fruiting bodies of typically early stage fungi (Laccaria vinaceoavellana). In the moderately burnt site, four EcM morphotypes were found, with dominance by one species, compared to a much more even EcM community in undisturbed forest where eight morphotypes were found.…”
Section: Commmentioning
confidence: 89%
“…Similarly, for inoculation experiments, such as that of Tata et al (2010), where EcM inoculum is already present in the soil, the benefits of inoculating seedlings are not clear, especially if the inoculated EcM species does not remain on the roots of the seedlings. This suggests that EcMs are most likely to benefit seedling performance when seedlings are planted in degraded areas where suitable EcM inoculum is not available, such as mine tailings (Lee et al 2008), burnt areas (Akema et al 2009), degraded peatlands (Turjaman et al 2007) or areas previously used for agriculture (Ingleby et al 2000). This suggests that EcMs are most likely to benefit seedling performance when seedlings are planted in degraded areas where suitable EcM inoculum is not available, such as mine tailings (Lee et al 2008), burnt areas (Akema et al 2009), degraded peatlands (Turjaman et al 2007) or areas previously used for agriculture (Ingleby et al 2000).…”
Section: Effects Of Ectomycorrhizal Colonization On the Growth And Pementioning
confidence: 99%
See 1 more Smart Citation
“…Laccaria vinaceoavellanea merupakan spesies JPE yang sebelumnya dilaporkan tersebar pada 3 negara yakni Jepang, Laos, dan Malaysia dengan 225 catatan keberadaan (GBIF, 2021). Sebelumnya, jamur ini sebenarnya telah dilaporkan menjadi salah satu JPE yang berkontribusi dalam perbaikan lahan hutan setelah terbakar di Kalimantan Timur (Akema et al, 2009). Zhang et al (2014) melaporkan bahwa spesies ini memiliki potensi yang baik sebagai agen mikorediasi karena mampu untuk mengakumulasi berbagai bahan berbahaya pada lingkungan tercemar.…”
Section: Laccaria Cf Vinaceoavellaneaunclassified